Operational transconductance amplifier-based comparator for high frequency applications using 22 nm FinFET technology - Vasudeva Gowdagere; Uma Bidikinamane Venkataramanaiah (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Fin field-effect transistor (FinFET) based analog circuits are gaining importance over metal oxide semiconductor field effect transistor (MOSFET) based circuits with stability and high frequency operations. Comparator that forms the sub block of most of the analog circuits is designed using operational transconductance amplifier (OTA). The OTA is designed using new design procedures and the comparator circuit is designed integrating the sub circuits with OTA. The building blocks of the comparator design such as input level shifter, differential pair with cascode stage and class AB amplifier for output swing are designed and integrated. Folded cascode circuit is used in the feedback path to maintain the common mode input value to a constant, so that the differential pair amplifies the differential signal. The gain of the comparator is achieved to be greater than 100 dB, with phase margin of 65°, common mode rejection ratio (CMRR) of above 70 dB and output swing from rail to rail. The circuit provides unity gain bandwidth of 5 GHz and is suitable for high sampling rate data converter circuits.